Quantitative inspiratory–expiratory chest CT findings in COVID-19 survivors at the 6-month follow-up - Jia, Xi; Han, Xiaoyu; Cao, Yukun; Fan, Yanqing; Yuan, Mei; Li, Yumin; Gu, Jin; Zheng, Yuting; Wang, Li; Qu, Yali; Shi, Heshui (Scientific reports, 2022)
We evaluated pulmonary sequelae in COVID-19 survivors by quantitative inspiratory–expiratory chest CT (QCT) and explored abnormal pulmonary diffusion risk factors at the 6-month follow-up. This retrospective study enrolled 205 COVID-19 survivors with baseline CT data and QCT scans at 6-month follow-up. Patients without follow-up pulmonary function tests were excluded. All subjects were divided into group 1 (carbon monoxide diffusion capacity [DL CO ] < 80% predicted, n = 88) and group 2 (DL CO ≥ 80% predicted, n = 117). Clinical characteristics and lung radiological changes were recorded. Semiquantitative total CT score (0–25) was calculated by adding five lobes scores (0–5) according to the range of lesion involvement (0: no involvement; 1: < 5%; 2: 5–25%; 3: 26–50%; 4: 51–75%; 5: > 75%). Data was analyzed by two-sample t-test, Spearman test, etc. 29% survivors showed air trapping by follow-up QCT. Semiquantitative CT score and QCT parameter of air trapping in group 1 were significantly greater than group 2 ( p < 0.001). Decreased DL CO was negatively correlated with the follow-up CT score for ground-glass opacity (r = − 0.246, p = 0.003), reticulation (r = − 0.206, p = 0.002), air trapping (r = − 0.220, p = 0.002) and relative lung volume changes (r = − 0.265, p = 0.001). COVID-19 survivors with lung diffusion deficits at 6-month follow-up tended to develop air trapping, possibly due to small-airway impairment.